Poetic language : theory and practice from the Renaissance to the present - Jones, Tom, 1975- (Edinburgh University Press, 2012)
The first study of poetic language from a historical and philosophical perspective In a series of 12 chapters, exemplary poems - by Walter Ralegh, John Milton,William Cowper, William Wordsworth, Gerard Manley Hopkins, Wallace Stevens, Ezra Pound, Frank O'Hara, Robert Creeley, W. S. Graham, Tom Raworth, Denise Riley and Thomas A. Clark - are read alongside theoretical discussions of poetic language. The discussions provide a jargon-free account of a wide range of historical and contemporary schools of thought about poetic language, and an organised, coherent critique of those schools (including analytical philosophy, cognitive poetics, structuralism and post-structuralism). Via close readings of whole poems from 1600 to the present readers are taken through a wide range of modernist, experimental and innovative poetries. Paired chapters within a chronological structure allow lecturers and students to approach the material in a variety of ways (by individual chapters, paired historical periods) that are appropriate to different courses. Key Features: Surveys a variety of linguistic and philosophical approaches to poetic language: analytical, cognitive, post-structuralist, pragmatic Provides readings of complete poems and places those readings within the wider context of each poet's work Combines theory and practice Includes a Glossary of Terms, Biographical Notes on Poets and Suggested Further Reading and Further Reading (by Theoretical School)